2015
DOI: 10.1177/0961203315615220
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes with multi-targeted immunosuppressive protocol in children with severe proliferative lupus nephritis

Abstract: We have previously reported the one-year outcomes of 16 children with severe proliferative lupus nephritis (LN) who were treated using a multi-targeted induction protocol based on intravenous (IV) pulse methylprednisolone (MP), mycophenolate mofetil (MMF) and cyclosporine (CSA). This study examined the long-term renal outcomes of these 16 children, followed up for a median duration of 9.2 years (range 5.8-14.2 years). Primary treatment outcome was complete renal remission. Secondary outcomes included patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Our study has few limitations, including that none of the patient had NIH-CI scores > 6. Nonetheless, our cohort is representative of other pediatric LN cohorts [51, 52], and all biomarker relationships and changes observed in our cohort were very likely due to LN, rather than comorbid conditions affecting the kidney. This is different from studies in adults with LN, who often suffer from other chronic system diseases that promote renal scarring, such as hypertension, diabetes, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 84%
“…Our study has few limitations, including that none of the patient had NIH-CI scores > 6. Nonetheless, our cohort is representative of other pediatric LN cohorts [51, 52], and all biomarker relationships and changes observed in our cohort were very likely due to LN, rather than comorbid conditions affecting the kidney. This is different from studies in adults with LN, who often suffer from other chronic system diseases that promote renal scarring, such as hypertension, diabetes, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 84%
“…A prospective randomized trial showed comparable outcomes between CSA and CYC in children (50). Retrospective data in children support the efficacy of sequential induction therapy with MMF followed by CSA for proliferative LN (51).…”
Section: Advances In Immunosuppressive Therapy For Lupus Nephritismentioning
confidence: 87%
“…While 90% of cSLE patients with class V LN in cSLE achieve renal remission, only 76% can maintain remission despite low dose oral corticosteroids and/or maintenance immunosuppression such as AZA or MMF (88,89). The rate of kidney flares due to SLE is 25-50% on therapy (51,84,89). Besides class IV LN, risk factors for development of ESKD include male gender, black race, hypertension, nephrotic syndrome, anti-phospholipid antibodies, high glomerular staining for MCP-1, chronicity on biopsy, poor response to induction therapy, and occurrence of nephritic kidney flare (23,87).…”
Section: Outcomes Of Lupus Nephritis In Children In 2016mentioning
confidence: 99%
“…18,28 The MPA-cyclosporine combination was demonstrated to be an effective induction therapy with a satisfactory safety profile. [29][30][31][32] Owing to unsatisfactory remission rates of standard management for LN endorsed by the ACR/EULAR, prospective studies are still required to verify the efficacy of MPA combination therapy. 22,27 In the present study, renal pathologic findings were not predictive of clinical remission.…”
Section: Discussionmentioning
confidence: 99%